Streamlined wildland-urban interface fire tracing (SWUIFT): Modeling wildfire spread in communities. (September 2021) - Masoudvaziri, Nima; Szasdi Bardales, Fernando; Keskin, Oguz Kaan; Sarreshtehdari, Amir; Sun, Kang; Elhami-Khorasani, Negar
Abstract: The wildland-urban interface (WUI) is defined as a geographic area where human developments and flammable vegetation merge in a wildfire-prone environment. Losses due to wildfire have been rising in the past decade, attributed to changes in vegetation growth, fuel availability, and increased land developments in WUI. This paper studies the process of wildfire spread inside WUI communities. The fire spread rate within WUI communities is determined for nine wildfires that were ranked among the most destructive wildfires in North America. An improved quasi-empirical model that considers radiation and fire spotting as modes of fire spread inside a community is proposed. The new model is validated using the documented spread rates during the 2007 Witch and Guejito fires and the 2017 Tubbs fire. The proposed model is computationally efficient and can be used to quantify fire spread rate and the number of affected structures inside a community during a wildfire event. Highlights: Communities are being exposed to faster spreading wildfires in recent years. A streamlined integrative urban fire spread model is proposed. The proposed model is applied to two case studies in California. The proposed model is capable of capturing fire progression in WUI communities when compared to real scenarios.